Efeitos de guerras civis sobre as populações de mamíferos e na dinâmica de caça - Braga-Pereira, Franciany Gabriella (2018)
Civil wars often coincide with areas of major importance in terms of global biodiversity and have plagued the everyday reality of many countries throughout human history. In this research, through the local ecological knowledge we assessed for the first time the main consequences of a prolonged civil war in Southwest Africa on forest and savannah mammals, using Angola as a case study. The country is home to at least 275 species of mammals, many of them historically hunted by the local communities before, during and after the intermittent 27-year Angolan civil war (1975-2002). We also have a major focus on Angola’s main protected areas, Quiçama National Park and Quiçama Game Reserve. In Chapter 1 when comparing post-war abundance of Quiçama’s mammals with pre-war baseline, we found a population depletion on 20 of 26 (77%) mammal species considered in this study, with some species experiencing a decline of up to 80% in the baseline abundance. In addition, this reduction was greater in open savannah landscapes than in forests, due to the greater accessibility and detection of large prey, and the efficient use of long-range projectiles in savannahs. Large-bodied mammals were preferred targets and had been overhunted, but as their populations became increasingly depleted, the size structure of prey species gradually shifted towards smaller-bodied species. Finally, we present a general flow diagram of how civil wars in low-governance countries can have both positive and negative impacts on native wildlife populations at different scales of space and time. We also show that currently, 36 countries worldwide are experiencing civil wars and most of these conflicts are either fuelled or funded by international interests or began after an external intervention. These internationalized conflicts are more prolonged and less likely to find a political resolution. Therefore, considering measures that can reduce the impact of warfare on wildlife, we emphasize the intentional or inadvertent complicity of foreign powers, which should promote policies that mitigate the detrimental environmental impacts of armed conflicts. In Chapter 2, our focus was to identify the hunting techniques used before, during and after the Angolan civil war in savannah and forest. We collected information on techniques used by the hunter to approach, pursue and capture game species. We found that rifles introduced by the Angolan civil war magnify the spectrum of species caught from small-bodied to large-bodied species, and might induce a mammalian population abundance erosion. We also found a clear species-specific conjunct of hunting techniques, valuing the cost-benefit of each approach. 10 The usage frequency of rifles was also higher in the savannah than in the forest. We also found changes over time for prey approximation and persecution techniques. The substitution of more rudimentary hunting techniques by modern techniques (ex.: from spears and net to rifles) is possibly guided to attend the animal trade chain, with people acting more independently and rationally according to their own interests, abandoning community hunting techniques and depleting some common resources. In Chapter 3, we focus more on the motivators of hunting. We assess the i) influence of prey species body size, trophic level, and sex and age class in hunter selectivity of wild mammals in Quiçama; ii) the primary motivation behind the pursuit of wild mammals; iii) the capture frequency and the seletivity of each species; and iv) the degree to which the illegal wildlife trade has been more profitable in the short term than alternative activities carried out by local resident hunters. Our results show that medium and large-bodied species, particularly adult males in markedly size-dimorphic species, when available are more selectively pursued by hunters mainly to maximize their bushmeat demand and obtain greater profits from the bushmeat trade. The main motivations behind hunting wild mammals were subsistence wild meat consumption, retaliation against livestock depredation and other conflicts, the bushmeat trade, and trade in other body parts. Trade in bushmeat and other by-products extracted from wild vertebrates ensured that local residents could earn higher domestic revenues compared to any alternative sources of direct and indirect income. However, these financial benefits were at best modest, largely unsustainable in terms of prey population crashes, and generated high long-term costs for the local to regional scale economy, the renewable natural resource capital and native biodiversity.